The CCI Creative City Index (CCI-CCI) - Hartley, John; Potts, J.; MacDonald, T. (University of International Business and Economics Press, 2012)
The CCI Creative City Index (CCI-CCI) is a new approach to the measurement and ranking of creative global cities. First, we argue for a new approach to creative cities, based on enterprise (in contrast to powerful or imperial cities), as ' zones of attraction. ‘We identify what makes a city creative (as opposed to merely ' global’), in order to isolate \what values are required to measure and compare creative cities. The index is constructed over eight principal dimensions, each with multiple distinct elements. Some of these dimensions are familiar from other global city indexes, such as the MORI or Ga WC indexes, which account for the size of creative industries, the scale of cultural amenities, or the flows of creative people and global connectedness. In addition to these indicators, the CCI-CCI contributes several new dimensions. These measure the demand side of creative participation, the attention economy, user-created content, and the productivity of socially networked consumers. Global creative cities can often seem alike, in respect of per-capita measures of factors such as public spending on cultural amenities, or the number of hotels and restaurants.This is to be expected when people and capital are relatively free to move, and where economic and political institutions are broadly comparable. However, we find that different cities can register far larger differences at the level of consumer-co-creation and especially digital creative 'microproductivity'. We set out the case for our new model of a creative city index by showing why greater attention to consumer co-creation and microproductivity are important, as well as examining how these factors have been previously overlooked. We show how we have measured these additional factors and indicate the effect they have on creative and global city indexes. We then present the findings from a pilot study of six cities, two Australian (Brisbane & Melbourne), two German (Berlin & Bremen) and two from the UK (Cardiff & London), to indicate how the new index is calculated and applied. Our results indicate much greater variance arising from the new arguments between cities.